Organic Manures and Bio-inoculants Mediated Influence on growth and Flowering of African Marigold (Tagetes erecta L.) cv. Pusa Narangi Gainda - K., Swathi; Sarkar, Indrajit; Maitra, Soumen; Sharma, Sachin (International Journal of Bio-resource and Stress Management, 2017)
Marigold (Tagetes sp.) is an ornamental annual suitable for commercial cultivation in Indian plains as a loose flower. West Bengal is considered as a prominent producer of this flower in India. In northern part of West Bengal due to suitability of agro-climatic condition enormous scope for commercial cultivation of African marigold has already been realized. The present experiment was carried out at Instructional Farm of Faculty of Horticulture under Uttar Banga Krishi Viswavidyalaya during winter season of 2015−2016 with the organic sources which are easily available eco friendly and sustainable. The experiment was laid out in Randomized Block design containing seven treatments comprising of poultry manure, farm yard manure, vermicompost, mustard oil cake and bio-fertilizer like Azotobactor, phosphorous solubilizing bacteria along with control replicated thrice with a seedlings of twenty eight days old were transplanted in a plot size of 2x2 m2 following a spacing of 45×30 cm2. Results revealed that application of organic sources at optimum dosage showed an increased and improved results interms of growth and flowering as compared to control. Among all the treatments poultry manure at 15 t ha-1 significantly improved the plant height, plant spread, branch production leaf chlorophyll content, earliness in flowering, duration of flowering, floriferousness, fresh weight of flowers and obviously the flower yield of African marigold followed by mustard oil cake application as foliar application.